Hepatitis E virus replication and interferon responses in human placental cells. Issue 2 (8th January 2018) - Knegendorf, Leonard; Drave, Svenja A.; Dao Thi, Viet Loan; Debing, Yannick; Brown, Richard J. P.; Vondran, Florian W. R.; Resner, Kathrin; Friesland, Martina; Khera, Tanvi; Engelmann, Michael; Bremer, Birgit; Wedemeyer, Heiner; et al.
Abstract : ‐ HEV genotype 1 and 3 strains are replicating in placental‐derived cell lines ‐ Placental‐derived JEG‐3 cells support full‐length HEV replication, viral assembly and release and are permissive for infection with HEVcc ‐ A differential tissue‐specific host response to HEV genotypes could be observed as the genotype 1 interferon‐α sensitivity was lower in the placental cells as compared to liver cells, which was not the case for HEV genotype 3 ‐ The interferon‐stimulated gene expression is downregulated by HEV in placental‐derived JEG‐3 cells Abstract : Hepatitis E virus (HEV) is a member of the genus Orthohepevirus in the family Hepeviridae and the causative agent of hepatitis E in humans. HEV is a major health problem in developing countries, causing mortality rates up to 25% in pregnant women. However, these cases are mainly reported for HEV genotype (gt)1, while gt3 infections are usually associated with subclinical courses of disease. The pathogenic mechanisms of adverse maternal and fetal outcome during pregnancy in HEV‐infected pregnant women remain elusive. In this study, we observed that HEV is capable of completing the full viral life cycle in placental‐derived cells (JEG‐3). Following transfection of JEG‐3 cells, HEV replication of both HEV gts could be observed. Furthermore, determination of extracellular and intracellular viral capsid levels, infectivity, and biophysical properties revealed production of HEV infectious particles with similar characteristics as in liver‐derived cells. Viral entry was analyzed by infection of target cells and detection of either viral RNA or staining for viral capsid protein by immunofluorescence. HEV gt1 and gt3 were efficiently inhibited by ribavirin in placental as well as in human hepatoma cells. In contrast, interferon‐α sensitivity was lower in the placental cells compared to liver cells for gt1 but not gt3 HEV. Simultaneous determination of interferon‐stimulated gene expression levels demonstrated an efficient HEV‐dependent restriction in JEG‐3. Conclusion : We showed differential tissue‐specific host responses to HEV genotypes, adding to our understanding of the mechanisms contributing to fatal outcomes of HEV infections during pregnancy. Using this cell‐culture system, new therapeutic options for HEV during pregnancy can be identified and evaluated. ( Hepatology Communications 2018;2:173–187)